A president report of The Ninth Scientific Meeting of Japan Association for Simulation-based Education in Healthcare Professionals (JASEHP) - Kaneko, Ichiro (Journal of Japan Association for Simulation-based Education in Healthcare Professionals, 2022)
The Ninth Scientific Meeting of Japan Association for Simulation-based Education in Healthcare Professionals (JASEHP) was held at TSERC in Teikyo University Itabashi Campus on Saturday, October 23, 2021. The concept of the meeting is “Developing the community of practice in the simulation for healthcare professionals “. In2021, the COVID-19 pandemic made it difficult to hold it face-to-face style. Therefore, this academic conference was held online. Despite the online event, a large number of participants participated, and sufficient discussions on simulation medical education were possible. Moreover, it was possible to activate the discussion by the invited speakers from foreign countries. The event was successfully held by the great support from the faculty members and members of JASEHP, TSERC staff, and the members of Teikyo University Medical Education Center (CMET). We are quite sure that a meaningful discussion was held by bringing together the cooperation of staff and related companies. The theme of this conference is a new proposal to extend the community of practice in simulation-based education for healthcare professionals, and it seems that it has achieved sufficient results as this conference to take the first step. And the usefulness of the online academic meeting for JASEHP seemed to have obtained the great result.